2017
DOI: 10.1177/1369433217706778
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of shear strength of reinforced concrete beams without shear reinforcement considering bond action of longitudinal reinforcements

Abstract: The shear strength of concrete beams without shear reinforcement is determined by the shear strength of the concrete compressive zone, the shear force due to dowel action, and the shear force due to aggregate interlock. The existing models and formulas to predict shear strength of concrete beams based on geometric theories related to beam action and arch action that only consider shear resistance in relation to arch action while neglecting dowel action and aggregate interlock have been unable to accurately exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…3) Contribution V a, was 17 % -24 %, V cz was 50 % -55 % which was in agreement with [12]. Hence it can be concluded that empirical formula holds good in determining the shear resistance of beams with transverse reinforcement provided.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3) Contribution V a, was 17 % -24 %, V cz was 50 % -55 % which was in agreement with [12]. Hence it can be concluded that empirical formula holds good in determining the shear resistance of beams with transverse reinforcement provided.…”
Section: Discussionsupporting
confidence: 77%
“…Further [12] had determined that effect of aggregate interlock was 15 % -25 % and dowel force was 20 % -27 % by keeping a'/d ratio constant and proposed an empirical formula as mentioned in Eqs. ( 2) and (3) to evaluate various components in shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…Further " Kim et al (2018)", had concluded that aggregate interlock effect was 15%-25% and dowel force was 20%-27% by keeping shear span to depth ratio constant and proposed an empirical formula to evaluate various components in shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…More than one mechanism is generally involved and the contribution of each in resisting shear has to be deciphered . The investigations on RC beams without stirrups are being carried out till date because failure of such beams is more brittle than RC beams with stirrups. However, in engineering practice shear reinforcement is usually provided in beams and so it is more relevant to investigate on shear behavior of RC beams with shear reinforcement.…”
Section: Introductionmentioning
confidence: 99%